Численно-полевой анализ эффективности эксцентриситета зазора под главными полюсами в двигателе постоянного тока с последовательным возбуждением - Милых, Владимир Иванович; Дзенис, Сергей Евгеньевич (НТУ "ХПИ", 2018)
Проведен численно-полевой анализ эффективности эксцентриситета зазора под главными полюсами в двигателе постоянного тока с последовательным возбуждением. При изменении эксцентриситета и самого зазора сравниваются электромагнитные параметры двигателя и распределение магнитной индукции в активной зоне. Уменьшение эксцентриситета и зазора не приводит к критическому повышению магнитной индукции под краями главного полюса из-за реакции якоря. Поэтому угрозы увеличения максимума межламельного напряжения на коллекторе не ожидается.

A numerical-field analysis of the eccentricity efficiency of the gap under the main poles in a DC motor with series excitation is carried out. With a change in the degree of eccentricity and the gap itself, the electromagnetic parameters of the motor and the distribution of magnetic induction in the gap and in the tooth-slot layer are compared. The research is carried out using the example of a 60 kW four-pole DC motor. The elimination of the eccentricity of the gap and its reduction in comparison with the basic design of the DC motor does not lead to a critical redistribution of the ma gnetic field in the core of the engine. This means that there is no excessive increase in magnetic induction under the edges of the main pole tip due to the reaction of the armature. Therefore, there is no threat of an increase in the local maximum of inte rlamel voltage on the collector. Consequently, it is possible to improve the efficiency of the DC motor. The use of identified reserves in the selection of the gap below the main poles will lead to a slight increase in the magnetic flux and the DC motor electromagnetic moment. The results of the analysis make it possible to improve the technique for designing DC machines.
A numerical-field analysis of the eccentricity efficiency of the gap under the main poles in a DC motor with series excitation
Keywords: главный полюс; магнитное поле; численные расчеты; магнитная индукция; электромагнитные параметры; DC motor; main pole; gap eccentricity; magnetic field; numerical calculations; magnetic induction; electromagnetic parameters